Analyzing Ethanol’s Antioxidant Extract of Pandanus Leaves through DPPH Method - Hardianti, Siti; Chiuman, Linda; Ginting, Chrismis Novalinda; Adrian, Adrian (International Journal Labs, 2022)
Background: Aging is a natural process and no one can avoid it. The aging process is also a physiological process that will occur in all living things. This process covers all organs of the body including the skin which is one of the body tissues that directly shows the occurrence of the aging process Aim: This research aims to analyze ethanol’s antioxidant extract of pandanus leaves through DPPH method. Method: This type of research is using experimental research designs to determine the antioxidant activity affected by time, and temperature with the DPPH method, a formulation of the effects of the ethanol extract of fragrant pandan leaves (Pandanus amaryllifous Roxb). Findings: It has active antioxidant activity and IC50 extract of fragrant pandan ethanol on the 5th day with a temperature of 50° C and on the 3rd day with a temperature of 35° C which is the best antioxidant activity.